Cetuximab strongly enhances immune cell infiltration into liver metastatic sites in colorectal cancer - Inoue, Yuka (Cancer Sci, 2017)
Cetuximab has activity against colorectal cancers. Recent studies demonstrated that cetuximab induces antibody‐dependent cell‐mediated cytotoxicity via immune cells, and a new immune‐related mechanism of inducing immunogenic cell death. This study aimed to evaluate the immune responses induced by cetuximab in tumor microenvironments at liver metastasis sites of metastatic colorectal cancer patients. We assessed immune cell infiltration in the liver metastatic sites of 53 colorectal cancer patients. These patients were divided into three groups according to the treatment before operation: chemotherapy with cetuximab, chemotherapy without cetuximab, and no chemotherapy. The inflammatory cells in the liver metastatic sites were assessed by hematoxylin–eosin staining, focusing on the invasive margin. The overall inflammatory reaction and number of lymphoid cells were assessed with a four‐point scoring system. We then assessed immune cell infiltration (CD3, CD8 and CD56) in 15 liver metastatic sites. Hematoxylin–eosin staining demonstrated more inflammatory cells in the chemotherapy with cetuximab group than in the other groups (P < 0.001). Of note, inflammatory cells were found in intratumoral areas, and the destruction of cancer cell foci was observed in the chemotherapy with cetuximab group. Moreover, a higher infiltration of CD3+ (P = 0.003), CD8+ (P = 0.003) and CD56+ (P = 0.001) cells was observed in the chemotherapy with cetuximab group than in the other groups. These results suggest that cetuximab might have an immune‐enhancing effect. As such, the immune‐related mechanism of action of cetuximab may enhance the efficacy of combination therapy, such as chemotherapy and immunotherapy using therapeutic peptides.